Association between Lifelines Diet Score (LLDS) and some novel anthropometric indices, including Body Roundness Index (BRI), A Body Shape Index (ABSI), Visceral Adiposity Index (VAI), and Body Adiposity Index (BAI), in Iranian women: a cross-sectional study - Matin Nazari; Khadijeh Mirzaie; Seyedali Keshavarz (BMC, 2024)
Abstract Background Anthropometry is a reliable method to assess obesity status, and previous studies have shown the association of several dietary quality scores with obesity using anthropometric indices. This study aimed to evaluate the association between LLDS and anthropometric measurements. Methods A total of 217 women between the ages of 18 and 48 participated in the study. Anthropometric values, biochemical tests, and body composition were assessed for each participant using standard protocols and methods. The LLDS was determined based on 12 components using a reliable and valid food frequency questionnaire (FFQ) that contained 147 items. Results We detected a marginally significant inverse association between the LLDS and VAI scores in the second tertile. Study participants in the second tertile of LLDS had lower odds of having high VAI than those in the reference tertile after adjusting for age, energy intake, physical activity, education, and economic status (OR: -0.16; 95% CI: -0.8, 0.06; P = 0.06). There was no statistically significant trend for the association between LLDS and all assessed anthropometric indices, including BRI, ABSI, VAI, and BAI, across tertiles of LLDS in the crude and all adjusted models (P-trend > 0.05). Conclusions There was no significant association between LLDS and some novel anthropometric indices, including BRI, ABSI, VAI, and BAI. However, after adjusting for probable confounders, a marginally significant inverse association between LLDS and VAI was detected.